The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.juro.2006.08.094
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Satisfaction Rates for the Redesigned 2-Piece Penile Prosthesis

Abstract: The redesigned Ambicor 2-piece penile prosthesis appears to be safe and effective. It is associated with a low rate of revision as well as high patient and partner satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 16 publications
5
64
2
Order By: Relevance
“…Several articles [17,22,40–42] refer to the acceptance of a secondary implant when the first implant fails (Table ). Caire et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles [17,22,40–42] refer to the acceptance of a secondary implant when the first implant fails (Table ). Caire et al.…”
Section: Discussionmentioning
confidence: 99%
“…As the fluid reservoir for the Ambicor is the proximal portion of the cylinders, the continued pressure on this area led to autoinflation of the device as the fluid was forced forward into the distal cylinders. While the Ambicor has a mechanical failure rate as low as 0.7 to 2.3% in previous studies [7, 8] the condition seen in this patient is a previously unreported complication and failure. One previous report describes a failure to deflate, although this was due to a blood clot near the corporal input tubing [9].…”
Section: Discussionmentioning
confidence: 59%
“…Actually PP provides a satisfactory, definitive solution for ED. In different patient satisfaction studies it was shown that, of the PP implanted men more than 90% stated they were still using the PP for sexual intercourse with an average frequency of coitus of 5 times monthly (8)(9)(10). A recent study conducted by Escasa et al supported previous studies and confirmed that sexual activity increases testosterone level which was more prominent in participants who had sexual intercourse (7).…”
mentioning
confidence: 68%